2013
DOI: 10.1080/00220388.2012.709621
|View full text |Cite
|
Sign up to set email alerts
|

Aid and Growth: What Meta-Analysis Reveals

Abstract: Recent literature in the meta-analysis category where results from a range of studies are brought together throws doubt on the ability of foreign aid to foster economic growth and development. This article assesses what meta-analysis has to contribute to the literature on the effectiveness of foreign aid in terms of growth impact. We re-examine key hypotheses, and find that the effect of aid on growth is positive and statistically significant. This significant effect is genuine, and not an artefact of publicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(78 citation statements)
references
References 36 publications
4
74
0
Order By: Relevance
“…The MDGs set goals, targets and indicators 3 Doucouliagos and Paldam (2009) found that aid had been ineffective in fostering economic growth. This finding was, however, challenged in a subsequent study by Mekasha and Tarp (2013), who re-examined the main hypothesis put forward by Doucouliagos and Paldam. In their study, Mekasha and Tarp expanded Doucouliagos and Paldam's metaanalysis to better reflect the economic statistical and data challenges.…”
Section: The Aid Effectiveness Agenda: Results Transparency and Accomentioning
confidence: 83%
“…The MDGs set goals, targets and indicators 3 Doucouliagos and Paldam (2009) found that aid had been ineffective in fostering economic growth. This finding was, however, challenged in a subsequent study by Mekasha and Tarp (2013), who re-examined the main hypothesis put forward by Doucouliagos and Paldam. In their study, Mekasha and Tarp expanded Doucouliagos and Paldam's metaanalysis to better reflect the economic statistical and data challenges.…”
Section: The Aid Effectiveness Agenda: Results Transparency and Accomentioning
confidence: 83%
“…Doucouliagos and Paldam (2011) find that oda is ineffective in promoting growth, while Mekasha and Tarp (2013) find that its effect on growth is positive and statistically significant. An extensive review of the literature demonstrates that the debate continues.…”
Section: Official Development Assistance and Economic Growthmentioning
confidence: 97%
“…According to them, if there was a positive effect of aid on growth it would be small and of economic little significance. But the conclusions they drew from meta-analysis were themselves strongly criticized by Mekasha and Tarp (2011). Using alternative technics and a slightly different sample, they show that the effect of aid on growth is positive and significant.…”
Section: Ideology Versus Methodologymentioning
confidence: 99%